The Star-spangled banner - Key, Francis Scott, 1779-1843.; Spier, Peter (Garden City, N.Y. : Doubleday, 1973)
Illustrates three verses of our national anthem, written at the battle of Fort McHenry during the War of 1812. Music is included.
Keywords: Star-spangled banner (Song); Star-Spangled Banner; Star-spangled banner (Song); United States -- History -- War of 1812.; United States -- History -- War of 1812.